Supplementary Effect of Ensiled Ficus Fruit [Ficus nota (Blanco) Merr.] on The Growth Performance in Mallard Ducks [Anas platyrhynchos (Linnaeus), 1758] - Gaviola, Isagani Q; Gacutan Jr., Manuel D.; Come, Warren D.; Yap, Karen Luz T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
A study was conducted to determine the effects of supplementing the ensiled ficus (EFF) fruit on the growth performance of mallard ducks. One hundred seventy-five (175) day old straight-run mallard ducklings were assigned with the following diets: A (control), B (5% EFF inclusion), C (10% EFF inclusion), D (15% EFF inclusion), and E (20% EFF inclusion) following Randomized Complete Block Design (RCBD) with cage location as blocking factor. Data were run in general linear model of SAS v.9.4. TS1M8 and difference among treatments were determined using trend comparison and declared significant at =0.05. Results showed the ensiling can improve the chemical composition of the ficus fruits and make it favorable to mallard ducks when supplemented. The effect of supplementing EFF in mallard ducks showed a general increase in VFI with higher inclusion rate of EFF with comparable BW and WG. However, FCR was a bit higher with ducks given increasing EFF supplement. Lastly, RFCC was also lower in diets with EFF compared to the control group.